Origin of Structures and Textures of some Kurdistan Marbles as Inferred from Sedimentary Ancestor Structures, NE-Iraq - Karim, KamaL Haji (Sulaimani Journal for Pure and Applied Sciences, 2004)
The Quarries of Iraqi Kurdistan metamorphic marbles (true marble) are distributed along a belt near and parallel to the Iranian border in northeastern Iraq. These marbles associated with low-grade pelitic and calc-schist (green schist facies) and phyllite. They are formed by regional metamorphism of different types of sedimentary parent rocks in an environment not exceeded that of green schist facies (400 C and 8kb). The pelitic equivalent of the Kurdistan calcitic marble contain chlorite, albite, muscovite and biotite. In the latter years, their economic value is rapidly increased as their polished slabs extensively used for decoration purpose. The beautiful features of these marbles are consisting of sophisticated mesoscopic structures of different shapes, size and colors originated from plastic flowage and mixing of different composition and impurities reflecting either the original depositional or diageneticallyintroduced materials. Before plastic flowage they suffered from burial and tectonic fracturing which later filled with spary calcite. The origin of the marbles is analyzed according to the stage of paragenesis of the structures such as foliation, banding (layering), flow structure. The field and lab studies proved that they are all retumed to relict of primary and secondary (Nagenetic) sedimentary sttuctures. The marbles suffered from various degrees of tendency toward homogenization as the grade of regional metamorphism progressed, this reflected by mixing of foreground and background together. In addition to diffused boundary of contrasting components. Although they resemble the banded and augen gneisses but no ones formed by metamorphic differentiation. Most of the precursor structures are related to pressure solution seams and stylolites, which are combined with the triangle of Walness which deal with solution seams. Other structures are returned to lamination of the sedimentary parent rocks. Finally the probable stratigraphic unit as the original parent rocks is discussed.
Keywords: Marble; pressure solution; sedimentary rocks; metamorphic rocks; metamorphic texture; metamorphic structure; metamorphic paragenesis; Walness; Kurdistan rocks; Commercial marble; true marble; paragenesis